A revised shock history for the youngest unbrecciated lunar basalt – Northwest Africa 032 - Mijajlovic, Tatiana; Xue, Xie; Walton, Erin L. (My University, 2020)
Northwest Africa (NWA) 032 is considered to be the youngest radiometrically-dated mare basalt, with concordant Rb-Sr and Sm-Nd ages of 2.947 ± 0.016 Ga and 2.931 ± 0.092, respectively [1]. These ages are ~175 Ma older than those from 40Ar39Ar (2.779 ± 0.014 Ga) [2]. NWA 032 contains a high modal abundance of pyroxene (50.7 vol%), plagioclase (29.4 vol%), and olivine (11.3 vol%) [3]. The texture is that of an unbrecciated olivine-pyroxene phyric basalt. Olivine phenocrysts are zoned with Mg rich cores (Fo34-50) and thin, discontinuous Fe-rich rims (Fo30). Fine grained (≤ 1μm) elongated, tapered plagioclase crystals (An80-90) are present within the groundmass, interspersed with pyroxene (En1-25Wo15-25) of similar shape and size. These two minerals occur in a plumose texture, radiating from a common nucleation point. Pyroxene may be categorized based on grain size as either groundmass (<1 μm), intermediate crystals (~50 μm) or larger phenocrysts (~100 μm) [3]. The mineralogy of NWA 032 makes it ideal for the study and classification of shock features based on the updated shock classification scheme [4], which relies on petrographic observations of deformation and transformation in olivine, pyroxene and plagioclase – the three most abundant minerals in NWA 032. A previous description of shock effects in NWA 032 allowed for a shock pressure estimate of ~40-60 GPa [3]; however, the shock state of plagioclase feldspar (shock-amorphized vs crystalline) was inconclusive, owing to the fine grain size of this mineral (≤1μm). The purpose of our study is to characterize the shock deformation and transformation effects in NWA 032 using a combination of field emission scanning electron microscopy (FESEM) and Raman spectroscopy, focusing on the shock state of feldspar, as well as characterizing the crystallization products of shock melting. The latter have been demonstrated as useful criteria to evaluate shock conditions [5]. Our results more tightly constrain the shock history experienced by NWA 032.
Presented on September 21-23, 2020 at the "GeoConvention 2020" virtual event.
Keywords: shock history; basalt; meteorites; NWA 032